Total Quality Management from the Personnel Perspective in Sports Organizations - Özcan, Buşra (Technium Social Sciences Journal, 2024)
The primary objective of this research is to explore the perspectives of personnel within sports organizations concerning Total Quality Management (TQM). Specifically, the study targets a sample comprising 127 voluntary institutional personnel employed at the Istanbul Directorate of Youth Services and Sports. To gauge the extent of TQM implementation, the ’Total Quality Management Implementation Factors Scale,’ developed by Balcı (2002), was randomly administered to this sample. The research delves into the levels of TQM implementation among the personnel of the Istanbul Directorate of Youth Services and Sports. The acquired data were scrutinized in correlation with variables such as gender, age, education level, duration of employment, title, and job satisfaction. The study investigates the implementation of Total Quality Management (TQM) among personnel at the Istanbul Directorate of Youth Services and Sports, utilizing the ’Total Quality Management Implementation Factors Scale’ developed by Balcı (2002). The research assesses TQM levels in relation to various variables, including gender, age, education level, duration of employment, title, and job satisfaction.